1992
DOI: 10.3109/02699059209034947
|View full text |Cite
|
Sign up to set email alerts
|

Problems and changes after traumatic brain injury: Differing perceptions within and between families

Abstract: This study is an attempt to characterize subgroups of families based on differing perceptions of problems and changes after traumatic brain injury. The Problem Checklist of the NYU Head Injury Family Interview was administered to 34 people with head injuries (PHI), and a significant other (SO) of each, between 1 and 3 years post-injury. Families were found to differ systematically in their responses and could be divided into three groups: High Agreement group (HAF), where there was high agreement between the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 8 publications
6
39
2
Order By: Relevance
“…These two subgroups, representing 67 percent of the entire sample, did not differ from each other in ratings of postinjury functioning for any of the eight KBCI scales. These findings are consistent with those of Cavallo et al [21] and Seel et al [22]. Nevertheless, Table 3 demonstrates the shift in concordance that occurred between self-and other raters from pre-to postinjury; other raters reported significantly greater problems postinjury than self-raters did, which is another indication of at least some degree of awareness problems subsequent to TBI.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These two subgroups, representing 67 percent of the entire sample, did not differ from each other in ratings of postinjury functioning for any of the eight KBCI scales. These findings are consistent with those of Cavallo et al [21] and Seel et al [22]. Nevertheless, Table 3 demonstrates the shift in concordance that occurred between self-and other raters from pre-to postinjury; other raters reported significantly greater problems postinjury than self-raters did, which is another indication of at least some degree of awareness problems subsequent to TBI.…”
Section: Discussionsupporting
confidence: 87%
“…For example, in individuals with primarily moderate to severe TBI, Cavallo and colleagues found that 39 percent of their patient and family member pairs were in high agreement about the patient's functioning 1 to 3 years postinjury on the Problem Checklist of the New York University Head Injury Family Interview [21]. High agreement was defined as agreement on the presence or absence of at least 75 percent of 34 common post-TBI problems.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it may be inadequate to generalize how all families described their experiences of being involved in inpatient TBI rehabilitation. This is consistent with the findings of Cavallo, Kay, and Ezrachi (1992), who identified that while all brain injuries impact the entire family, not all families react to or are affected by it in the same way. Similarly, every participant in our study described the overall experience of being involved as one that was overwhelming, lifechanging, shocking, and full of uncertainties.…”
Section: Qualitative Themessupporting
confidence: 92%
“…As a first step towards addressing the question of who will provide the best information, a number of researchers have investigated outcomes from TBI by comparing responses between persons with TBI and a family member (or close friend) on questions about their life situation (McKinlay & Brooks, 1984;Brooks, Campsie, Symington, Beattie & McKinlay, 1987;Dodwell, 1988a;Dodwell, 1988b;Hendryx, 1989;Brown & Nell, 1992;Cavallo, Kay, & Ezrachi, 1992;Burton & Volpe, 1993;Kaitaro, Koshkinen & Kaipio, 1995;Tennant, Macdermott & Neary, 1996;Tepper, Beatty & DeJong, 1996). Despite the considerable work done in this area a number of important issues remain.…”
Section: Introductionmentioning
confidence: 99%